Are preterm-born survivors at risk of long-term respiratory disease?. (July 2017) - Kaczmarczyk, Katarzyna; Wiszomirska, Ida; Szturmowicz, Magdalena; Magiera, Andrzej; Błażkiewicz, Michalina
Background: To evaluate the long-term impact of preterm birth on respiratory function in female patients born preterm, we undertook spirometric examinations twice, as they reached the age of puberty, then follow-up examinations of part of the same cohort in adulthood. We sought evidence that preterm birth is correlated with poorer spirometric results into adulthood. Methods: A total of 70 girls (aged 12.2 ± 1.5 years in 1997) who had been born preterm (at 34.7 ± 1.86 weeks, none having experienced bronchopulmonary dysplasia) took part in spriometric examinations in 1997 and again in 1998. Of those, after a gap of 17 years, a group of 12 were successfully recontacted and participated in the 2015 examination as adults (then aged 27.6 ± 2.6 years, born at 34.5 ± 1.92 weeks). We compared spirometric results across the adolescent and adult examinations, and compared the adult results with an adult reference group. Results: The percentage values of FEV1 (forced expiratory volume in 1 s), FVC (forced vital capacity) and MVV (maximal voluntary ventilation) showed significant improvement between the two examinations in the early adolescent period. In adulthood, FEV1 %pred (percentage predicted forced expiratory volume in 1 s) showed no statistically significant difference. The mean values of both FVC and FVC%pred (percentage predicted forced vital capacity) for the preterm-born group were lower than for the reference group, but this was not statistically significant. The preterm-born group showed lower values of such parameters as forced expiratory flow at 25–75% of FVC, MEF25 (maximal expiratory flow at 25% of forced vital capacity) and FEV1 /FVC as compared with the reference group, but again without statistical significance. Conclusions: (1) A somewhat below-norm level of respiratory parameters among preterm-born girls entering pubescence may attest to continued negative impact on their respiratory system. (2) A significant improvement in their spirometric results 1 year later may indicate that pubescence helps compensate for the earlier negative effect of preterm birth. (3) No significant differences were seen in lung function in preterm-born adults as compared with a reference group of adults, although the preterm-born group did exhibit lower values of all parameters studied and more frequent obstructive disorders.